Optimalisasi Patroli Roda Dua Satuan Sabhara Dalam Mencegah Tindak Pidana Curanmor Di Wilayah Hukum Polres Kuningan - Ady Christofol Rumbobiar (Indonesian Journal of Police Studies, 2020)
This research was conducted based on the existence of motor vehicle theft (curanmor) that occurred in Kuningan District. As the holder of the prevention function, Sabhara is one of the Police Technical Functions that is responsible for reducing the problem of fraud. This research was conducted to examine the development of chanting, the implementation of Sabhara R2 patrols and optimization of Sabhara R2 patrols in Kuningan District. In discussing this research, the author uses the theories and concepts that have been used including: management theory, crime prevention theory and patrol concept as a knife of analysis. The approach used is a qualitative approach and the method used is the method of field research. Source of data / information that I use is primary data that is the result of interviews and secondary data that is data obtained from books that are related to the thesis of the author. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. From the results of the study, the implementation of patrols using two-wheeled vehicles at the Kuningan police station has been carried out in accordance with procedures including the preparation, implementation and termination stages, but there are still obstacles encountered in carrying out patrols namely lack of fuel budget, lack of personnel, community participation in providing information about the situation of the conditions around the environment, especially regarding the problem of fraud, and geographical location. To optimize the two-wheeled patrol, an additional budget is needed to support the implementation of the patrol. The advice given by the author is to prioritize walking patrol, collaborate with the community and related agencies to work together to make it easier to control situations and conditions and superiors give rewards to members in the successful implementation of the task.